Recent progress and strategies for enhancing photocatalytic water splitting - Li, Y; Tsang, SCE (Elsevier, 2020)
Solar light-driven water splitting provides a promising way to store and use abundant solar energy in the form of gaseous hydrogen which is the cleanest chemical fuel for mankind; therefore this field has been attracting increasing attention over the past decades. The fundamental steps for efficient photocatalyst for water splitting include uptake of photons of targeted energy range by appropriate electronic band structure, excited electrons and holes (excitons) migration, as well as recombination and selective conversion excited electrons for H+ reduction to H2 and holes and OH− to O2 on catalyst surface. Each step if not efficiently taken place could hamper the overall photocatalytic activity. Numerous semiconductors with appropriate bandgaps have mainly been developed as candidates for effective solar energy capture, whereas at present, their low quantum efficiency still remains as the major obstacle in further applications. In this minireview, we will disentangle the progress to develop photocatalysts with good photon uptake from photocatalytic water splitting performance. In accordance with the thermodynamic and kinetic considerations of the photocatalytic water splitting reaction, different strategies for improving the fundamental processes have been briefly reviewed. Some recent advances in facilitating charge carriers separation have also been presented. Photocatalytic water splitting at elevated temperatures is emphasized as a novel approach to suppress photo-excitons recombination on catalyst surface owing to adsorption of enhanced concentration of ionic species including H+ and OH− to create their local polarization to the excitons. Stronger polarization to hinder the excitons recombination can also be obtained by using polar-faceted support materials to the active phase of semiconductor. It is clearly demonstrated in this minireview that such high temperature–promoted photocatalytic water splitting systems could open up a new direction and provide a new innovation to this field.